Discordant Phylogenomic Placement of Hydnoraceae and Lactoridaceae Within Piperales Using Data From All Three Genomes - Jost, Matthias; Samain, Marie-Stéphanie; Marques, Isabel; Graham, Sean W.; Wanke, Stefan (Frontiers in Plant Science, 2021)
Phylogenetic relationships within the magnoliid order Piperales have been studied extensively, yet the relationships of the monotypic family Lactoridaceae and the holoparasitic Hydnoraceae to the remainder of the order remain a matter of debate. Since the first confident molecular phylogenetic placement of Hydnoraceae among Piperales, different studies have recovered various contradictory topologies. Most phylogenetic hypotheses were inferred using only a few loci and have had incomplete taxon sampling at the genus level. Based on these results and an online survey of taxonomic opinion, the Angiosperm Phylogeny Group lumped both Hydnoraceae and Lactoridaceae in Aristolochiaceae; however, the latter family continues to have unclear relationships to the aforementioned taxa. Here we present extensive phylogenomic tree reconstructions based on up to 137 loci from all three subcellular genomes for all genera of Piperales. We infer relationships based on a variety of phylogenetic methods, explore instances of phylogenomic discordance between the subcellular genomes, and test alternative topologies. Consistent with these phylogenomic results and a consideration of the principles of phylogenetic classification, we propose to exclude Hydnoraceae and Lactoridaceae from the broad circumscription of Aristolochiaceae, and instead favor recognition of four monophyletic and morphologically well circumscribed families in the perianth-bearing Piperales: Aristolochiaceae, Asaraceae, Hydnoraceae and Lactoridaceae, with a total of six families in the order.